Green oliva on TV: the advent of color television by military regime in Brazil (Tempo e Argumento, 2021)
This article aims to address the determination of the military regime for the implementation of color television in Brazil. For that, we used the bibliography on the subject and journalistic articles of the periodicals: O Estado de S. Paulo, Diário de S. Paulo, O Globo, Jornal do Brasil and Veja. Therefore, we aim to bring the interests of the military to light in color television, such as: greater control over the television sector, pioneering in South America, technological advancement and incentive to national industry.